Design, synthesis and evaluation of novel 2, 2-dimethyl-2, 3-dihydroquinolin-4(1H)-one based chalcones as cytotoxic agents. Issue 9 (September 2018) - Jean, Julie; Farrell, David S.; Farrelly, Angela M.; Toomey, Sinead; Barlow, James W.
Abstract: We designed and synthesised a series of novel chalcones, incorporating the heterocyclic framework of 2, 2-dimethyl-2, 3-dihydro-4(1H)-quinolinone, which was prepared via Sonogashira coupling of a substituted orthoaniline under aqueous conditions using Pd catalysis followed by acid-mediated cyclisation. The compounds were screened against the NCI-N87 and DLD-1 cancer cell lines, with most compounds showing low micromolar cytotoxic activity.